Prenatal sonographic features of fetal atelosteogenesis type 1 - Luewan S. (2014)
Atelosteogenesis is a lethal chondrodysplastic disorder characterized by severe micromelia and spinal abnormalities, including a heterogeneous group of disorders with overlapping phenotypic features.1,2 Three subtypes have been described on the basis of radiologic and pathologic findings. Type 1 has pathologically unique giant cell chondrodysplasia. Type 2 has similar humeral and femoral bone shapes but typically has a hitchhiker thumb or toe and distinctive chondro-osseous histopathologic features caused by the diastrophic dysplasia sulfate transporter gene, whereas types 1 and 2 are caused by the filamin B gene. Type 3 has less dysmorphic facial features and well-ossified but disharmonious short tubular bones. Atelosteogenesis type 1, a synonym for spondylohumerofemoral hypoplasia, is a rare chondrodysplastic disorder caused by mutations in filamin B located at 3p14.3,4 This gene has an important role in vertebral segmentation, joint formation, and endochondral ossification. It is characterized by severe rhizomelia with bowing of the limbs, especially the humeri, femurs, proximal and middle phalanges, and fibulas, with distal tapering and delay in ossification of vertebrae.1,5 Other clinical hallmarks of the disorder include midface hypoplasia, micrognathia with a cleft palate, and a narrow thorax, leading to pulmonary hypoplasia and laryngeal stenosis, attributable to the lethality. 1,5,6 Histopathologic findings are hypocellular and acellular areas and occasional giant cells in the resting cartilage, similar to boomerang dysplasia. 1,5,7 Because atelosteogenesis type 1 is usually lethal, prenatal diagnosis is desirable for proper management. To our best knowledge, only 4 cases have been prenatally diagnosed and reported in the literature. 6,8-10 Here we present the prenatal sonographic features of atelosteogenesis to add to the number of cases, which may be helpful in diagnosis when skeletal dysplasia is encountered. © 2009 by the American Institute of Ultrasound in Medicine.